United Arab Emirates : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that United Arab Emirates has continued to benefit from its perceived safe haven status and large fiscal and external buffers that have helped limit negative spillovers from lower oil prices, sluggish global growth, and volatility in emerging market economies. Non-oil growth remained robust at 4.8 percent in 2014, driven by construction. The economic outlook is expected to moderate amid lower oil prices. Non-oil growth is projected to slow to 3.4 percent in 2015, before increasing to 4.6 percent by 2020, supported by the implementation of mega projects and private investment in the run-up to Expo 2020.